The Effect of Using Flashcard to Improve Language Skills in Children with Speech Delay (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2022)
Language is one of the essential aspects of life because it is a communication tool used in interacting with social beings. One of the aspects of early childhood language development is speaking. The ability to speak is essential for children to meet their communication needs. Speech delay is a tendency that is difficult to feel when you want to convey information or interact with other people. This study aimed to determine whether the use of picture word card media can affect the language improvement of children who experience speech delay. The type of research used is single-subject research. The independent variable in this study is the therapy of giving picture word cards, and the dependent variable is language ability. The subjects in this study were children aged three years who experienced speech delay. The data collection method used observation, which refers to aspects of language development that consist of understanding, expressing, and literacy. Analysis of the data used in the analysis of paired sample T-test and descriptive in the form of tables and graphs. The results of this study indicate that the use of picture word cards can significantly improve language skills in children with speech delay, with t = -5.382 and p = 0.001 <0.05. The data analysis is the analysis of paired sample T-test and descriptive in the form of tables and graphs. The results of this study indicate that the use of picture word cards can significantly improve language skills in children with speech delay, with t = -5.382 and p = 0.001 <0.05. The data analysis is the analysis of paired sample T-test and descriptive in the form of tables and graphs. The results of this study indicate that the use of picture word cards can significantly improve language skills in children with speech delay, with t = -5.382 and p = 0.001 <0.05.